THE SPACE OF ETHNONATIONAL IDENTITIES OF KAZAKHSTAN SOCIETY: PRINCIPLES AND MODELS OF STRATIFICATION - DUNAEV, Vladimir; BIZHANOV, Akhan; SHAYKEMELEV, Mukhtarbek (CENTRAL ASIA AND THE CAUCASUS, 2019)
The authors discuss the general patterns and specific features of shaping ethnocultural and national identities within the multiethnic society of contemporary Kazakhstan. For the first time in Kazakhstan’s political sociology, the issue is examined using a methodology that applies to constructing reflexive analytical social space models. They present a model of interethnic cooperation space stratification in the republic based on seven fundamentally important features. The authors analyze the singularities of the Kazakhs’ subethnic identity space during the emergence of a common Kazakhstan identity and reveal the role of the Assembly of the People of Kazakhstan as a unique form of institutionalized organization of civil and ethnocultural identity space.